(untitled) (Journal of Hama University, 2022)
Purpose: This study aimed to compare fracture resistance between Endocrown and conventional crowns reinforced with fiber posts when subjected to pressure forces.The sample consisted of 20 intact maxillary first bi-radicular premolars, freshly extracted for orthodontic reasons. Teeth were similar in size and length almost, Endodontically treated and equally distributed into two groups. Then all premolars crowns were cut and flattened so that they remained 2 mm above the cemento enamel junction. Group A: 10 premolars were prepared to be restored by lithium disilicate glass ceramic Endocrown. Group B: 10 premolars were prepared to be restored by conventional crowns retained with fiber posts which were made of same materials. All crowns were cemented by dual cure polymerized resin cement with a self-etching system and then subjected to pressure test by using a general mechanical testing machine. Each sample was loaded until fracture and the data was recorded by Newton. Samples failure modes were examined by stereoscope with (10) magnification and radiography. Then the data statistically analyzed. Independent T-student test was used to compare the mean values between groups. Chi square was used to compare the failure modes between the groups.mean max load values were (914.20) N in group A and (734.20) N in group B. T-Student test showed that P-Value less than 0.05, confidence level 95% so there was significant difference between groups. Group A showed significantly higher fracture resistance forces mean than group B. within the limits of this study, all the forces of fracture were much higher the maximum chewing forces in the upper premolars region. Endocrown showed higher mean values than conventional crowns so can be considered as a conservative option for restoring Endodontically treated premolars with 2 mm remaining dental tissue. Much more root fractures were also observed for higher fracture strength values (escort for group A).